2021
DOI: 10.4081/tz.2021.105
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Dioon edule cycad seeds by rodents in a tropical oak forest in Mexico

Abstract: Predation of seeds of the cycad Dioon edule Lindl. by Peromyscus mexicanus (Saussure, 1860) has been previously documented, demonstrating that the seeds’ toxins are not harmful when combined with a varied diet. However, there is scarce evidence of P. mexicanus as a seed disperser. In a tropical oak forest in San Luis Potosí, Mexico, we experimented with seeds of D. edule and Quercus polymorpha Schltdl. & Cham., evaluating predators’ preference and recording it with photo-trapping. Burrows were sampled in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The low diversity of visitors reported here is consistent with other studies focused on cycads, where seed removal is carried out by a low diversity of small mammals, almost specifically ( Burbidge and Whelan 1982 , Snow and Walter 2007 , Hall and Walter 2013 , Yáñez-Espinosa et al 2021 , Monteza‐Moreno et al 2022 ). In addition, most of the species that interact with the cone represent sporadic visits ( Burbidge and Whelan 1982 , Snow and Walter 2007 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The low diversity of visitors reported here is consistent with other studies focused on cycads, where seed removal is carried out by a low diversity of small mammals, almost specifically ( Burbidge and Whelan 1982 , Snow and Walter 2007 , Hall and Walter 2013 , Yáñez-Espinosa et al 2021 , Monteza‐Moreno et al 2022 ). In addition, most of the species that interact with the cone represent sporadic visits ( Burbidge and Whelan 1982 , Snow and Walter 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…Three small mammals, the mouse, southern spotted skunk and the kinkajou, are reported here as potential seed dispersers of Ceratozamia norstogii . Mice as dispersers have also been observed in other species of cycads ( González-Christen 1990 , Snow and Walter 2007 , Yáñez-Espinosa et al 2021 ), but the spotted skunk and the kinkajou biting and carrying cycad seeds are recorded for the first time. Our results showed that the mouse of the genus Pteromiscus was a frequent visitor to the female cone of Ceratozamia norstogii and was observed biting and carrying seeds sarcotesta for several nights and for a long time, even when the cone was disintegrated and the seeds scattered on the ground (Figs 4 , 5 , 6 ,Suppl.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations